PENDAMPINGAN GURU DALAM PENYUSUNAN LKPD DAN BAHAN AJAR KONTEKSTUAL UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI SMAN 18 BONE - Rahmatullah; Sandi; Adam Rahman Suradi; Nurhana; A.Novi Fitriani Lunir; Ari Afrizal; Nurfadillah; Lisa Firna; Alim Nur; Muh. Alief Tito Rahman; Ahmad Muhaeming; Susi Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This community service program aimed to improve teachers’ competencies in developing contextual Student Worksheets (LKPD) and teaching materials at SMAN 18 Bone. The program was initiated in response to the limited use of contextual learning resources and the challenges faced by teachers in designing instructional materials aligned with students’ characteristics and the principles of the Merdeka Curriculum. A participatory mentoring approach was employed, involving 15 teachers as the main participants and 60 students as indirect beneficiaries of the implementation process. The program consisted of needs assessment, training sessions, workshops, product development, mentoring and revision activities, as well as evaluation. Data were collected through pretest and posttest assessments, observations, and documentation. Quantitative data were analyzed using a Paired Sample t-Test, while qualitative data were analyzed descriptively. The results showed that all research instruments were valid and reliable, with Cronbach’s Alpha values of 0.873 and 0.891. The Shapiro–Wilk normality test indicated that the data were normally distributed (p > 0.05). The average competency score increased from 65.57 in the pretest to 81.67 in the posttest, representing an improvement of 16.10 points. Furthermore, the Paired Sample t-Test revealed a statistically significant difference between pretest and posttest scores (t = -225.186; p < 0.001). These findings demonstrate that the mentoring program was effective in enhancing teachers’ abilities to develop contextual worksheets and teaching materials, thereby supporting more meaningful, student-centered, and effective learning processes